Introdução à geometria diferencial e à análise complexa - Silva, Rodrigo Thomaz da (Universidade Federal de São Carlos, 2021)
The paper "Conformal geometry, Euler numbers, and global invertibility in higher dimensions”, by Frederico Xavier, crosses different areas of Mathematics in order to obtain its main result. Among them we have Differential Geometry and Complex Analysis. So, in looking for a better preparation to read the cited paper, this work gathers great part of our study of both areas. We emphasise firstly curves and surfaces, and then complex analytic functions.
Introduction to differential geometry and complex analysis
Keywords: Análise; Analysis; Curves; Curvas; Geometry; Geometria; Funções analíticas; Analytic functions; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE::ANALISE COMPLEXA; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA::GEOMETRIA DIFERENCIAL